After Midlife, What Next? Rethinking Future Orientations, Belonging, and Success Among Executive Expatriates in Singapore - Hsu, Leslie; Tripathi, Shilpi (Advances in Social Sciences Research Journal, 2025)
This paper explores how executive expatriates navigate post-midlife transitions by re-evaluating their sense of success, belonging, and future direction. Drawing from qualitative interviews with midlife professionals living and working abroad, the study reveals a shift in priorities from achievement-driven identities to values rooted in emotional connection, legacy, and existential meaning. Using Interpretative Phenomenological Analysis (IPA), we uncover key themes such as disillusionment with career-defined success, the longing for deeper community integration, and emerging aspirations for retirement, contribution, and self-actualization. These insights reveal an urgent need for organizations and policymakers to support the aging expatriate population with holistic frameworks that address both career wind-down and psychosocial transitions.